Aptamer-guided luminous microsphere for anchoring and lightening Salmonella enterica serovar Typhimurium - Du, Han; Zhang, Xu; Yao, Mingru; Yang, Qingli; Wu, Wei (Sensors and actuators. B, Chemical, 2022)
Aptamers are recognition elements that are easy to synthesize and store, but their softness makes their stability and affinity subject to the influence of the environment. Herein, by taking advantage of the aptamer-specific ability to recognize targets and the fluorescence of nontoxic carbon dots (CDs), we constructed aptamer-guided luminous microspheres (~200 nm in size). These microspheres, with tetrahedral DNA (Td) as the skeleton, can actively recognize Salmonella enterica serovar Typhimurium (S. Typhimurium) and fluoresce after sensitively binding to the target. The fluorescence intensity emitted by the microspheres increased 3.05 times. The limitation of detection was 9 CFU/mL, with a detection range of 10–108 CFU/mL, and the recovery rate in qualified pasteurized milk and drinking water samples was 95.35–103.01%. Additionally, this presented fluorescence signal amplification strategy provides novel insights into the analysis of various food threat factors and other fluorescence imaging applications. [Display omitted] •Tetrahedron-aptamer DNA fluorescent microspheres are first prepared.•A signal amplification system for non-toxic quantum dot was constructed.•This strategy provides new insights for other fluorescence imaging.